2007
DOI: 10.1074/jbc.m609725200
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate, a Green Tea Polyphenol, Mediates NO-dependent Vasodilation Using Signaling Pathways in Vascular Endothelium Requiring Reactive Oxygen Species and Fyn

Abstract: Green tea consumption is associated with reduced cardiovascular mortality in some epidemiological studies. Epigallocatechin gallate (EGCG), a bioactive polyphenol in green tea, mimics metabolic actions of insulin to inhibit gluconeogenesis in hepatocytes. Because signaling pathways regulating metabolic and vasodilator actions of insulin are shared in common, we hypothesized that EGCG may also have vasodilator actions to stimulate production of nitric oxide (NO) from endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
141
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(157 citation statements)
references
References 62 publications
14
141
0
2
Order By: Relevance
“…33) EGCG also stimulates activation of endothelial nitric oxide synthase (eNOS) through activation of PI3K/Akt pathway. 34) These findings suggest that the modification of PI3K activation by flavonoids is different for concentrations, cell types, and classes of stimulants.…”
Section: Discussionmentioning
confidence: 97%
“…33) EGCG also stimulates activation of endothelial nitric oxide synthase (eNOS) through activation of PI3K/Akt pathway. 34) These findings suggest that the modification of PI3K activation by flavonoids is different for concentrations, cell types, and classes of stimulants.…”
Section: Discussionmentioning
confidence: 97%
“…12) Phosphorylation of eNOS at Ser-1177 has been found to be associated with increases in enzyme activation and NO production. 15) Furthermore, several studies have reported that polyphenols such as epigallocatechin-3-gallate, 21) delphinidin, 22) resveratrol, 23) and PAs from grape skin extract 24) increased the phosphorylation of eNOS. Evaluation of persimmon leaf PA-stimulated phosphorylation in HUVECs revealed that ex vivo persimmon leaf PAs at the maximal relaxation concentration caused time-dependent phosphorylation not only of eNOS (Ser-1177), but also of its upstream kinase Akt (Ser-473) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…18) Although these effects of polyphenol treatment could be secondary to its protective effect against oxidant stress, there is preliminary evidence indicating that polyphenols themselves may contribute to regulation of the vascular tone. 19) When administered in vitro, resveratrol (RV) enhances endothelial vasorelaxation by potentiating NO synthase and increasing the phosphorylation of Akt and endothelial nitric oxide synthase (eNOS), suggesting that RV alone has a vasodilatory effect. 19) We hypothesized that short-term treatment with polyphenols improves endothelial dysfunction related to diabetes.…”
mentioning
confidence: 99%
“…19) When administered in vitro, resveratrol (RV) enhances endothelial vasorelaxation by potentiating NO synthase and increasing the phosphorylation of Akt and endothelial nitric oxide synthase (eNOS), suggesting that RV alone has a vasodilatory effect. 19) We hypothesized that short-term treatment with polyphenols improves endothelial dysfunction related to diabetes.…”
mentioning
confidence: 99%